Trade, value chain technology and prices: Evidence from dairy in East Africa - Ignowski, Liz; Minten, Bart; Swinnen, Johan; Van Campenhout, Bjorn; Vandevelde, Senne (LICOS Centre for Institutions and Economic Performance, 2021)
Agricultural value chains, particularly in the developing world, have been going through drastic changes over the past decades. Differences in world market participation and access to value chain technologies might however have resulted in uneven experiences across countries. In this paper, we explore their impact on milk prices in the value chain, using the example of two East African countries, Ethiopia and Uganda. We develop a conceptual framework and then validate the model using unique primary price data collected at several levels in the dairy value chains in both countries. We find that prices are overall significantly lower in Uganda than Ethiopia, reflecting their respective net exporting and importing status. Moreover, despite shorter value chains, we find much more significant effects of distances from the capital (the major end destination) on milk prices in Ethiopia than in Uganda. This is likely linked to the widespread presence of milk chilling centers in Uganda. While i